Health education in the preparation of pregnant women for delivery in Primary Care: Integrative review (Research, Society and Development, 2023)
Introduction: Health education is fully linked to prenatal care, with the main objective of promoting the health of pregnant women, and it is up to the professional to develop educational measures that can change behaviors. For this reason, this study analyzed the evidence available in the literature on the preparation of pregnant women in prenatal care at usual risk, for the moment of vaginal delivery. Methodology: The methodology chosen is an integrative review (IR) that will seek, through national and international scientific production, to answer the guiding question of this study: What evidence is available in the literature on preparing pregnant women for childbirth through education and health? Inclusion criteria: textual productions published in Portuguese and English, available from June 2012 to June 2022, on the subject. Exclusion criteria: literature review articles will be disregarded. The analysis and synthesis of the data were carried out descriptively with the characteristic data of each study recorded in tables. Results: 3 articles were selected, analyzed by title and abstract, for full reading. Final considerations: Health education programs for pregnant women, provided by trained professionals, should be considered a natural part of the prenatal routine. The act of reproducing knowledge for pregnant women decreases fear of childbirth, anxiety and stress, as well as increases self-efficacy at the time of parturition.